Multi–scale enhancement mechanisms of graphene oxide on styrene–butadiene–styrene modified asphalt: An exploration from molecular dynamics simulations. (October 2021) - Hu, Kui; Yu, Caihua; Yang, Qilin; Chen, Yujing; Chen, Guixiang; Ma, Rong
Graphical abstract: Highlights: SBS-modified asphalt showed better viscoelastic properties via 0.3 wt% graphene oxide addition. Internal micro-state structures of modifier and base asphalt were enhanced. Absorption of modifier to low molecular weight compounds was increased. The experiments phenomenon and performance evaluation were better understood by molecular dynamics simulation. Abstract: The objective of this research is to clarify the mechanism of interaction between graphene oxide (GO) and styrene–butadiene–styrene (SBS) modified asphalt. In this paper, the GO/SBS–modified asphalt was prepared using GO with contents of 0.1 wt%, 0.3 wt%, and 0.6 wt%. The dynamic mechanical analysis (DMA) test was applied to characterize the viscoelastic properties of the asphalt. Fluorescence microscopy and atomic force microscopy (AFM) were employed to observe the internal structure and interface enhancement. Fourier transform infrared spectroscopy (FTIR) was used to determine whether some compounds were removed from the base asphalt based on the variations of the functional group. Furthermore, molecular dynamic simulations were performed to understand the subject and conduct the performance evaluation of the experiments. The results explain the interaction mechanism between GO and SBS–modified asphalt and provide multi–scale insights into the performance evaluation for the design of modified asphalt polymer materials.